A voltage balanced back-to-back stacked multicell converter - Sharma G.; Kapoor A.K. (My University, 2025)
This paper presents a voltage-balancing back-to-back stacked multicell converter (B2B-SMC) topology, which is easy to implement, does not require auxiliary capacitor charging circuit and can be easily extended for the increased number of levels. Unidirectional switches are added in the B2B-SMC to maintain the voltage across the capacitors. The advantages of the B2B-SMC over flying capacitor multilevel converter (FCC) and stacked multicell converter (SMC) are increased number of levels in the output voltage, low voltage total harmonic distortion (THD), lower switching losses, and reduced filter requirement. The B2B-SMC consist of two conventional stacked multicell converter (SMC), which are connected back-to-back using two low-switching frequency switches. Simulation results of a 33-level B2B-SMC are provided to verify the proposed topology for voltage-balancing of capacitors at different modulation indices. © 2016 IEEE.